Effectiveness of geometric quality control using a distance evaluation method. (2nd October 2019) - Zelasco, José F.; Donayo, Judith
ABSTRACT: Research studies have shown that when the error of a digital elevation model (DEM) is accepted as random, one of the two solutions is generally used. One is the employment of a benchmark, and the other is measuring the vertical distance to evaluate the vertical error. For the first solution, a benchmark or adequate random sample may be unavailable. The second solution consists of measuring only the vertical distance from a point of the DEM to the surface of the reference DEM. This solution provides only a biased vertical error. In this paper, a perpendicular distance evaluation method (PDEM) is proposed. This approach allows estimating the vertical error, and under certain irregular terrain conditions, the horizontal error. Simulations are presented in detail, starting from a real reference DEM, with 100 000 points. The results confirm that, the more irregular the terrain is, the better the horizontal error results, and that the evaluation of the vertical error is not biased.